The Effect Of Adding Carboxy Methyl Cellulose (Cmc) On The Characteristics Of Orange Sweet Potato Jam - Kholizah, Winda; Holinesti, Rahmi; Gusnita, Wiwik; Mustika, Sari (Universitas Negeri Padang, 2024)
This Study aims to analyze the effect of addition Carboxy Methyl Cellulose (CMC) as much as 0%, 0.5%, 1%, 1.5% and 2% on the quality of color, aroma, soft texture, easy to spread texture and taste of orange sweet potato jam. This type of research is a pure experiment using a Completely Randomized Design method consisting of 5 treatments and 3 repetitions. To analyze the quality of orange sweet potato jam, an organoleptic test was carried out involving 3 expert panelists. The data obtained was then tabulated and continued with ANOVA. If F count > F table then proceed with the Duncan test. The results of this research show that the addition of CMC has an effect on the quality of the soft texture and the texture is easy to spread. Meanwhile, the quality of color, aroma and taste has no effect. The results of data analysis obtained the highest overall achievement scores, namely color 3.67 (2%), aroma 3.67 (2%), easy to spread texture 4.00 (2%), soft texture 4.00 (2%), and taste 4.00 (2%). The best quality test results for orange sweet potato jam with the addition of CMC were in treatment X4 with the addition of 2% CMC.